Наративний прийом калейдоскопа як текстотвірна стратегія постмодерністської нелінеарної оповіді, центрованої на персонажеві (на матеріалі французького художнього дискурсу XXI ст.) - Савчук, Руслана Іванівна; Savchuk, R. I. (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті окреслено й проаналізовано роль наративного прийому калейдоскопа в конструюванні й форматуванні французької постмодерністської оповіді. З метою визначення особливостей застосування наративного прийому калейдоскопа як однієї з основних наративних текстотвірних стратегій з’ясовано закономірності розгортання французької постмодерністської нелінеарної оповіді, центрованої на персонажеві. The article outlines and analyzes the role of narrative technique of kaleidoscope in French postmodernist narrative constructing and formatting. For the purpose of determining general peculiarities of the narrative technique of kaleidoscope application as one of the principal narrative text forming strategies are found out the regularities of the development of French postmodernist nonlinear narrative, focused on the character. By the way of example of XXI century French literary discourse is proved that the narrative technique of kaleidoscope makes possible the narration formatting with parallel events and/or actions, forming in that way a complicated space of symmetrical worlds.
Narrative technique of kaleidoscope as text forming strategy of postmodernist nonlinear narrative, focused on the character (on the material of French literary discourse of XXI century)
Keywords: текстотвірна стратегія; text forming strategy; наративний прийом калейдоскопа; narrative technique of kaleidoscope; оповідь; narrative